Dekonstruksi Mitos Manyucuak Rantiang di Bukik Lontiak pada Masyarakat Sumpur Kudus - Wulandari, Shindi Amanta; Muliati, Roza (Jurnal Ilmiah Global Education, 2024)
The manyucuak rantiang tradition is a unique tradition that is only found in Sumpur Kudus, Sijunjung Regency. This tradition applies to immigrants, which is done by sticking a tree branch in Bukik Lontiak. The people of Sumpur Kudus believe that disaster will befall them if immigrants do not carry out this tradition. This research is qualitative research conducted in the Sumpur Kudus area, Sijunjung Regency, with data collection methods consisting of observation, interviews, and documentation. The author carries out analysis using cultural theory and deconstruction theory. The research results show that the manyucuak rantiang tradition has existed in the Sumpur Kudus area since the arrival of Islam in the 16th century AD, which was first brought by Sheikh Ibrahim. This tradition began with the habit of Sheikh Ibrahim who always stuck his buffalo palacuik in Bukik Lontiak, and the people who saw it imitated this habit so that manyucuak rantiang grew and became the culture of the Sumpur Kudus people. This tradition has undergone such changes from ancient times to the present, giving rise to pros and cons among the people of Sumpur Kudus. The Manyucuak Rantiang tradition is dismantled from the perspective of deconstruction theory. It has several new texts that deconstruct old texts that have been developing, namely: 1). As a form of respect for Sheikh Ibrahim, 2). As a way of communicating, 3). As a political strategy.